Effects of vasoactive therapy in patients with sensorineural hypoacusis - Rančić, Dejan; Todorović Јоvan; Mladenović, Marija (Medical Word, 2020)
Hearing loss is one of the most common health problems which is manifested by a subjective feeling of impaired hearing, the impossibility of listening in noise, intermittent or constant tinnitus. It can be conductive or sensorineural type (SNHL). Sensorineural hearing loss is caused by degeneration of the cochlea, which is responsible for the transduction of sound stimuli into nerve impulse. The aim of this study was to determine the effects of the applied vasoactive and hemokinetic therapy in people with sensorineural hypoacusis who refused embedding hearing aids. This retrospective study included 51 patients, which were in a three-year period in Clinic of Otorhinolaryngology KC Nis diagnosed with sensorineural hearing loss. Patients were clinically evaluated on the basis of the findings of otoscopy and tonal audiometry. Patients were treated with pentoxifylline, vitamins B1 and B6, cinnarizine (older than 50 years) and betahistine (younger than 50 years), for 28 days. After the treatment, using pure tone audiometry, we monitored the frequency of 125-8000 Hz and improvements in decibels. Controls were in 3 to 4 weeks. For analyzing and processing we used the worst finding and the best answer. Applied therapy led to improvements in all frequencies, particularly at high frequencies (2-8 kHz) (p < .001). Subjective symptoms such as tinnitus were absent, or were losing their intensity. Patients had a subjective feeling of better auditory functionality (better communication, better hearing experience of environment). In our study, we demonstrated that administration of vasodilators and hemokinetics in the treatment of patients with SNHL has positive effects in all frequencies, especially at high frequencies (2-8 kHz).